A Review on Molecular Dynamics Simulation of Joining Carbon-Nanotubes and Nanowires: Joining and Properties - Zaenudin, Mohamad; Abdulrazaq, Mohammed N.; Al-Zubaidi, Salah S. (International Journal of Integrated Engineering, 2022)
Carbon-nanotubes (CNTs) and Nanowires (NWs), the two nanomaterials with outstanding properties, are the materials with which their behaviour and properties have long been drawing attention to researchers. However, the tiny nature of these two materials causes difficulties in describing and estimating their behaviour and properties, thus a numerical technique that considers the tiny nature of the materials like Molecular Dynamics (MD) simulation is a promising solution to this problem. Since the early utilization of MD simulation in the investigation of the behaviour of carbon-nanotubes and nanowires, it provides the researcher with an excellent description of how the two materials behave at atomic-scale and then estimate their properties. Recently, MD simulation of CNTs and NWs exhibit growth in the simulation size as with the growth of the computing capabilities. The size of the materials being simulated by MD simulation increased significantly in the recent year, thus giving possibility to achieve a better description of the behaviour and a more precise estimation of the properties. In this review, we provide an overview of the recent advances in the investigation of the joining processes and properties of carbon-nanotubes and nanowires at atomic-scale utilizing molecular dynamics simulation.